VARIASI BAHASA DALAM LANSKAP LINGUISTIK DI KEBUN BINATANG SURABAYA - Agustin, Sherly Widya; Yarno; R. Panji Hermoyo (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
Linguistic landscape is a linguistic study that examines the use of language in public spaces. Language variation is defined as a form of language use that is different from a speaker. The emergence of language variations is motivated by the existence of a multilingual and multicultural society in Indonesia. This research aims to describe the use of language variations, language contestation, the function of these languages ​​and the sign-making linguistic landscape at the Surabaya Zoo. This research method uses descriptive qualitative with observation and photography data collection techniques. The data obtained is in the form of images containing language signs of the linguistic landscape. The research results found seven language variations at the Surabaya Zoo with three monolingual language variations, two bilingual language variations, and two multilingual language variations. The linguistic landscape sign makers at the Surabaya Zoo are from public and private authorities/individuals. The function of the linguistic landscape at the Surabaya Zoo namely, as a marker for buildings and rooms; as a medium of guidance and information; as a medium of prohibition and warning; as well as as a medium for distributing advertising. Keywords: linguistic landscape, language variations, surabaya zoo.